2019
DOI: 10.1002/jpen.1741
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis Between Computed Tomography and Surrogate Methods to Detect Low Muscle Mass Among Colorectal Cancer Patients

Abstract: Background We aimed to evaluate the agreement between computed tomography (CT) and surrogate methods applied in clinical practice for the assessment of low muscle mass. In addition, we assessed the association between different muscle‐assessment methods and nutrition status, as well as the prognostic value of low muscle mass on survival in patients with colorectal cancer (CRC). Methods This is a cohort including 188 CRC patients with 17 months’ follow‐up (interquartile range: 12–23 months) for mortality. Low m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 32 publications
1
18
0
1
Order By: Relevance
“…An earlier study has tested criterion-validity on the question of food intake, and found a good association with energy-and protein intake measured with 24 h recall [23]. The physical examination part showed good agreement with low muscle mass assessed by CT, in an out-patient clinic for colorectal cancer patients in Brazil [24]. In contrast, low agreement between PG-SGA and muscle mass assessed by BIA, was found among colorectal patients in Norway, especially among overweight persons [25].…”
Section: Implications Of the Translated And Culturally Adapted Toolmentioning
confidence: 88%
“…An earlier study has tested criterion-validity on the question of food intake, and found a good association with energy-and protein intake measured with 24 h recall [23]. The physical examination part showed good agreement with low muscle mass assessed by CT, in an out-patient clinic for colorectal cancer patients in Brazil [24]. In contrast, low agreement between PG-SGA and muscle mass assessed by BIA, was found among colorectal patients in Norway, especially among overweight persons [25].…”
Section: Implications Of the Translated And Culturally Adapted Toolmentioning
confidence: 88%
“…Additionally, we subjectively assessed a minimum of four of a possible seven muscle sites to determine a reduction in muscle stores rather than an objective measure such as bioelectrical impedance analysis (BIA) which all may have led to malnutrition under-reporting. However the physical assessment from the PG-SGA has demonstrated the best agreement with the gold standard computed tomography (CT) determined muscularity compared to other surrogate tools used in the clinical setting [ 30 , 31 ], and therefore is a clinically relevant measure. Importantly, the PG-SGA is commonly used in clinical practice in the oncology setting, whilst resources and tools to obtain objective measures, such as CT scans and BIA scales are less available and therefore less likely to be utilised.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cachexia is a multifactorial syndrome known for involuntary weight loss concomitant with reduced skeletal muscle mass, with or without loss of adipose tissue, being associated with decreased function, physical performance and a negative prognosis [8,9]. It happens as a result of a negative energy-protein balance, reduced food intake and an increased catabolic process, being aggravated by the systemic inflammation syndrome that often takes place in cancer patients [8][9][10][11][12]. The worsening of the cachectic condition leads to a progressive impairment of muscle function, which may explain its association with dynapenia in these patients [13].…”
Section: Introductionmentioning
confidence: 99%